Improved preventive maintenance in the framework of forecasting problem under subcontractor constraint. Issue 16 (18th August 2017) - Hajej, Zied; Rezg, Nidhal; Gharbi, Ali
Abstract : The paper presents a new improved preventive maintenance strategy for a forecasting problem of production and maintenance optimisation under subcontractor constraint. In order to satisfy the customer, the manufacturing system consists of a principal machine M 1 and called upon subcontractor machine M s . Knowing that both machines are subjected to random failures, failure rate of main machine increases with time and according to production rates. An improved preventive maintenance strategy is used for control of the machine M 1, whereas subcontractor machine M s is uncontrollable from preventive maintenance point of view. An analytic formulation of problem has been proposed in order to determine the economical production plans for M 1 and M s . An improved maintenance strategy (IMS) is developed in order to minimise the total production loss, when the subcontractor machine is unavailable. It consists of determining the best time to perform preventive maintenance actions taking into account production rates, history of M 1 and the state of subcontractor machine M s . Numerical results and sensitivity analysis are presented to highlight the performance measure and the usefulness of the IMS.